2002
DOI: 10.1097/01.asn.0000013294.11876.80
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Anemia Management among US Hemodialysis Patients

Abstract: Abstract. This study was undertaken to describe the relationship between hematocrit (Hct) and changes in the prescribed dose of erythropoietin (EPO) as well as selected patient and process care measures across annual national samples of hemodialysis patients from 1994 to 1998. This study uses the cohorts identified in the ESRD Core Indicators Project, random samples of 6181, 6241, 6364, 6634, and 7660 patients, stratified by ESRD Networks drawn for each year from 1994 to 1998. Patient demographic and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 38 publications
1
46
0
1
Order By: Relevance
“…The 2000 NKF-KDOQI guidelines recommend parenteral iron repletion for many hemodialysis (HD) patients whose hemoglobin levels are below target levels, and maintenance parenteral iron dosing is now recommended for the majority of HD patients. United States Renal Data System (USRDS) data reveal a steady increase in use of parenteral iron in incident and prevalent HD patients from 1994 to 1998 (4,5).…”
mentioning
confidence: 99%
“…The 2000 NKF-KDOQI guidelines recommend parenteral iron repletion for many hemodialysis (HD) patients whose hemoglobin levels are below target levels, and maintenance parenteral iron dosing is now recommended for the majority of HD patients. United States Renal Data System (USRDS) data reveal a steady increase in use of parenteral iron in incident and prevalent HD patients from 1994 to 1998 (4,5).…”
mentioning
confidence: 99%
“…The achievement of these favorable results has required increasing amounts of epoetin (1,4). On the one hand, there is a biologic need for more hormone to attain higher hematocrit levels; on the other hand, there are factors that can blunt the response to epoetin and therefore increase epoetin usage.…”
mentioning
confidence: 99%
“…Coladonato et al (1) noted that a 17.2% increase in epoetin dose was needed to increase the hematocrit 9.7% from 31.1% to 34.1%. The authors consider this a disproportionate increase in epoetin and attempt to verify this by using a nonphysiologic term, "EPO Resistant Index".…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Coladonato et al 12 also used the ESRD core indicator project and observed a similar difference in hematocrit between African Americans and whites (32.2 versus 32.6%), but no difference in EPO dose, after adjustment for predialysis weight. However, predialysis weights in their cohort were significantly higher for African Americans than whites, 11 suggesting that total EPO use may have been higher among African Americans.…”
Section: Discussionmentioning
confidence: 87%